Malay wood carving: plant species as inspiration / Liliwirianis N. ... [et al.] - N., Liliwirianis; Md Isa, Nurun Nadhirah; Khazai, Siti Norafiza; Md. Jan, Sarah Laila (2023)
One of the most essential aspects of traditional Malay culture is the art of Malay woodcarving. This study examines plant species that inspired crafters in their wood carving motif. Numerous plant species had inspired the crafter especially plant species that can be easily be found in the Malay environment. Some of the inspiration comes from plant species that consist of medicinal values, beauty, and symbolism. The discovery of these plant species will help future crafters comprehend how earlier Malay crafters created the pattern and how their beliefs were translated into their creative work. Malay traditional aesthetic features are distinctive.